Feeling you, when you feel me: attachment, empathic concern, and interpersonal emotion regulation. Issue 6 (2nd November 2022) - George-Levi, Sivan; Laslo-Roth, Roni; Schmidt-Barad, Tomer
ABSTRACT: Empathic concern is an important part of social relationships. Attachment orientation may explain individual differences in empathic concern. However, the circumstances under which attachment orientation is related to empathic concern remain unexamined. This exploratory study investigated the moderating role of a novel aspect of emotion regulation, interpersonal emotion regulation, in the relationship between attachment orientation and empathic concern. Study 1 ( N = 179) and Study 2 (direct replication, N =  202) yielded consistent main effects for emotion regulation. Interpersonal emotion regulation efficacy (people's belief that interpersonal emotion regulation can effectively change their negative and positive emotions) was positively associated with empathic concern. Avoidant attachment showed a moderately consistent negative association with empathic concern. Negative efficacy moderated the association between anxious attachment and empathic concern only in Study 1. The findings focus attention on the importance of interpersonal emotion regulation efficacy to empathic concern and on the complex relationship between attachment and empathic concern.